USABILITY EVALUATION SIMAK SILIWANGI UNIVERSITY USING HEURISTIC EVALUATION AND WEBUSE APPROACH - Andi Nur Rachman; Euis Nur Fitriani Dewi; Reynaldi Akbar Maulana; Arif Muhamad Nurdin (Jurnal Teknik Informatika (Jutif), 2022)
Sistem Informasi Akademik (SIMAK) of Siliwangi University is one of the information systems developed by UPT TIK, Siliwangi University. SIMAK must be able to become a website that is easy to use, has informative value, and has a high level of usability. User experience in using and operating it can be a measure of acceptance of SIMAK. Based on previous research, it is stated that SIMAK still does not meet the expectations of users. Therefore, in this study usability evaluation was carried out based on the Heuristic Evaluation and Web Usability Evaluation (WEBUSE) approaches. This study discusses the results of usability analysis based on the results of data collection from questionnaires distributed to 100 respondents who are active students (S1), lecturers, and staff at Siliwangi University. The results of usability measurements based on the Heuristic Evaluation method obtained usability points of 70.74% and the results of usability measurements based on the WEBUSE method obtained usability points of 67.84%. The results of usability measurements based on the Heuristic Evaluation and WEBUSE methods have consistent results which state that the SIMAK UNSIL website has a usability level of "Good". However, in some variable indicators there are still indicators that have low values, therefore it is necessary to make improvements based on the recommendations given to improve SIMAK quality.